"Marketing Problems And Solutions For Small Tea Growers In Golaghat District" (Journal of Namibian Studies : History Politics Culture, 2023)
The research paper investigates the supply chain management challenges faced by small tea growers in Golaghat District, Assam, with a specific focus on marketing problems. Through a mixed-methods approach comprising a literature review, field surveys, and case studies, this paper identifies key challenges, including broker and middlemen dominance, inefficient processing and storage facilities, transportation bottlenecks, and limited market access. Drawing insights from successful case studies, the paper proposes practical solutions to empower small tea growers and enhance the overall efficiency of the tea supply chain. The recommended strategies encompass the establishment of farmer cooperatives, upgrading processing and storage facilities, strengthening transportation infrastructure, promoting sustainable practices, engaging in policy advocacy, and embracing digital marketing platforms. By implementing these recommendations, small tea growers can tap into international markets, boost profitability, and fortify India's position in the global tea industry.